Pendokumentasian Aplikasi Ragam Hias Toraja sebagai Konservasi Budaya Bangsa pada Perancangan Interior - Amarena Nediari; Grace Hartanti (Bina Nusantara University, 2014)
Various ornaments of Indonesia come from ethnic groups from all over the archipelago. As a tangible culture, ornament has specific purpose and does not change throughout the ages. Tana Toraja is one ethnic group in the archipelago that has beautiful decorative art and one of the most popular tourism destinations in Indonesia. Toraja’s ornament generally is seen as decorative carving on the column of Tongkonan (Toraja traditional house), window, or even in barn doors. The beauty of Tana Toraja is not only as an inspiration for its colors and sculptures but also the variety of forms that has been simplified in the ornament. Moreover, the geometric forms are easy to apply as interior element in modern buildings. Generally, the value of these ornaments has a specific purpose related to the cultural and social custom of the Toraja people. Hence, the application needs to consider about the purpose of the symbol of the ornament.